Level of Information Need for BIM Models: Australia, New Zealand and ISO 19650 - Zima, Krzysztof; Mitera-Kiełbasa, Ewelina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Publishing BIM standards can facilitate the implementation of BIM construction projects. Their compilation, as in the article, allows to improve them, create or specify requirements. The publication of the international standard ISO 19650 for BIM resulted in numerous revisions to national guidelines. In the aspect of the degrees of detailing of BIM model is visible the development of their definition. Initially, they were divided according to the project phases, over time, into industries, and finally within the types of elements and separately for geometric and alphanumeric information, as well as the attached documentation. ISO 19650 uses the term Level of Information Need. Due to the quantity of global standards in various countries, the article focuses on the Oceania area and ISO 19650.
Keywords: information need; BIM Model; level of detail; LOD; degrees of detailing; BIM standard; BIM requirement; informacja; model BIM; poziom detali; stopień szczegółowości; standard BIM; wymagania BIM